FERNÁNDEZ LÓPEZ, J. A. (2022). Estudios de pensamiento medieval hispanojudío. Madrid: Comillas. - David Soto Carrasco (Daimon)
Reseña de FERNÁNDEZ LÓPEZ, J. A. (2022). Estudios de pensamiento medieval hispanojudío. Madrid: Comillas.